2012
DOI: 10.3856/vol40-issue3-fulltext-5
|View full text |Cite
|
Sign up to set email alerts
|

Control of Branchionus sp. and Amoeba sp. in cultures of Arthrospira sp.

Abstract: ABSTRACT. Cultivation of cyanobacterium Arthrospira sp. has been developed in many countries for the production of proteins, pigments and other compounds. Outdoor mass cultures are often affected by biological contamination, drastically reducing productivity as far as bringing death. This study evaluates the control of Branchionus sp. and Amoeba sp. with two chemical compounds: urea (U) and ammonium bicarbonate (AB), in laboratory conditions and outdoor mass culture of Arthrospira sp. The lethal concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…If one or a few contaminating species can be determined, contamination control can be acquired gradually based on previous experience from references and well-designed laboratory and outdoor experiments. Méndez and Uribe [11] reported that the application of 60 mg/L urea or 100 mg/L ammonium bicarbonate completely inhibited the grazing of Branchionus sp. and Amoeba sp., and did not affect the growth of Spirulina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If one or a few contaminating species can be determined, contamination control can be acquired gradually based on previous experience from references and well-designed laboratory and outdoor experiments. Méndez and Uribe [11] reported that the application of 60 mg/L urea or 100 mg/L ammonium bicarbonate completely inhibited the grazing of Branchionus sp. and Amoeba sp., and did not affect the growth of Spirulina.…”
Section: Discussionmentioning
confidence: 99%
“…However, the occurrence, population dynamics and impact of microzooplankton on microalgal culture has not well been studied [11][12][13]. In practice, many control strategies have been proposed to overcome the challenges of biological contamination: for instance, zooplankton predators of a relatively large size can be washed out by reducing the retention time of the algal culture [14], or removed using different sizes of mesh in algal pond [15][16][17][18], or treated with sonication [19]; but in most cases specific chemicals are utilized to control zooplankton contamination in mass algal cultures [11,20,21]. It is also worth mentioning the important study of Post et al [22], who demonstrated that lowering salinity could mitigate the effects of amoeba and ciliates in a Dunaliella pond.…”
Section: Introductionmentioning
confidence: 99%
“…It seems that ammonium bicarbonate is the most effective agent for exterminating rotifers. The ammonium toxicity is related to nonionized ammonia, which can exterminate most of the rotifers (Méndez and Uribe 2012). However, growth inhibition of microalgae caused by ammonia also occurs (Yuan et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Most approaches rely on the culturing of extremophiles under highly selective growth conditions (Borowitzka 2005) with regards to pH or, in the case of marine species, salinity, with the latter having the potential double benefit of stimulating productivity while suppressing increases in invader populations (Bartley et al 2013). Other methods can include filtration and the use of chemical pesticides (Bacellar Mendes and Vermelho 2013; Wang et al 2013; McBride et al 2014), although the former can only work when predators are relatively large, while imprudent use of pesticides can destroy the microalgae along with the predator (Méndez and Uribe 2012). Pulsed electric fields, intended to cause structural and functional damage to predators while leaving the microalgal cells intact, have also been suggested (Rego et al 2015).…”
Section: Introductionmentioning
confidence: 99%